Reflection of Marsiya Tradition in the Works of Abay Kunanbaev (Journal of Oriental Studies, 2020)
One of the unified phenomena of the worldview among the Kazakhs is the custom to express condolences, to mourn the deceased. Mourning is an inheritance that shows the socio-cultural value of the people, passing from generation to generation. From birth, the Kazakh people are those who love and value relatives. And it can show it at any moment. Peaceful and humble showing courtesy to his loved ones. The Kazakh people also went through disaster and joy in their history. One of the difficulties encountered in human life is death. Like life with or without honor, death can be with honor or without honor, and it will continue. A person who has reached his old age at death says goodbye to loved ones and utters his last words. Reads the admonition. After death, such actions as crying, announcing, interrupting speech, calming down, expressing condolences, reading a blessing, mourning are carried out. In Kazakh literature, meeting is not only like folklore. He always took place in all literary genres and in the works of Kazakh thinkers. In this very article, we decided to investigate that topic in the work of Abai that has not yet been investigated, this topic is a religious ceremony of mourning an Islamic Sharigat who died in a circle. Key words: Abay, iman, Marcia, tradition, death, fate.